WORK CULTURE AS A MEDIATOR: THE IMPACT OF THE WORK ENVIRONMENT AND COMPENSATION ON TEACHER PERFORMANCE AT THE FIRDAUS FOUNDATION, MAROS REGENCY - Salmah Harun; Azwar Wijaya Syam; Sufardi (Universitas Islam Lamongan, 2024)
This study aims to investigate the influence of the work environment and compensation on the performance of teachers with work culture as mediators at the Firdaus Foundation. Using a quantitative approach with path analysis (Partial Least Squares, PLS), this study involved a sample of 32 teachers. The results of the study show that the work environment and compensation have a significant influence on work culture. However, work culture does not have a significant effect on teacher performance, and the work environment also does not have a significant impact on teacher performance directly. In addition, the indirect influence of the work environment on teacher performance through work culture is not significant, and work culture cannot mediate the influence of compensation on teacher performance. Although compensation showed a significant influence on teacher performance, these results did not support the hypothesis that compensation directly affected teacher performance. This study concluded that although work environment and compensation variables have a significant effect on work culture, work culture and work environment do not directly affect teacher performance. The originality of the research lies in the use of work culture as a mediator in the context of the influence of work environment and compensation on teacher performance, providing new insights that are different from the findings of previous research.